Maternal health problems such as depression and anxiety and parent-child interaction - Sarah Liliane Goergen; Margarete Bolten; Martin Schröder; Marc Schmid; Christina Stadler (Archives of Depression and Anxiety - Peertechz Publications, 2018)
Background: The emotional climate between mothers and their children is known to be a significant indicator for the development of childhood psychopathology. One index that allows measuring family-emotional climate is the expressed emotion measure (EE). Maternal mental strain is known to affect maternal EE, as it can shape the way a mother thinks about, and interacts with her child.  Context and purpose of the study: The main objective of our study was to highlight the links between maternal EE, mother-child interaction and maternal mental problems on behavior problems in children.  Data were examined from 49 children aged 5 to 7 and their mothers. The Five-Minute Speech Sample (FMSS) was used to evaluate maternal EE. Behavioral disorders have been assessed with the German version of the Child Behavior Checklist (CBCL-4/18). To evaluate maternal symptoms of psychopathology, we used the German version of the Brief Symptoms Inventory (BSI). The quality of the mother-child interaction was observed during a standardized problem-solving task.  Results: High maternal criticism was linked to more child psychopathology, more maternal mental health problems, less maternal sensitivity and less responsiveness in children during the interactional task. The effect of maternal mental problems on externalizing problems in children was mediated by high criticism in mothers.  Conclusions:The results highlight noteworthy links between mother's criticism, child psychopathology and mother-child interactional patterns. According to our results, intervention programs focusing on children, mother-child-interaction and maternal psychopathology seem to be of major importance.